Discards in global tuna fisheries - Gilman, Eric; Suuronen, Petri; Chaloupka, Milani (Inter-Research, 2017)
Monitoring live and dead discarded catch contributes to effective fisheries management and ecological and socioeconomic sustainability. We determined contemporary rates and levels of discards in global tuna fisheries. An estimated 265 279 t (52 283 to 478 275 t 95% CI) is annually discarded by global tuna fisheries, composing about 5% of the weight of the total catch. Pelagic longline and purse seine fisheries contributed about 64 and 36% of discards, respectively. Other gear types composed <1% of discards. Discards in tuna fisheries are now 63% lower than estimated 1 decade earlier, mainly due to large declines in discards in longline tuna fisheries, possibly from increased retention of formerly discarded species and sizes of catch and increased gear selectivity. The decline also resulted, in part, from employing different methods to categorize caught sharks whose fins were retained and carcasses discarded following processing. Discard rates were greater in shallow- than deep-set longline fisheries, and higher in purse seine sets associated with fish aggregating devices and other floating objects than in other purse seine set types. The quality and availability of data on discards in global tuna fisheries were extremely limited. Filling gaps in monitoring, improving observer data fields and collection protocols, and providing public access to amalgamated discard data held by fisheries management organizations will improve the certainty of future discard estimates, sup orting effective management of discards in global tuna fisheries.
Keywords: discards; regional fisheries management organization; RFMO; fisheries; tuna